Autism-Associated Variant in the SLC6A3 Gene Alters the Oral Microbiome and Metabolism in a Murine Model - DiCarlo, Gabriella E.; Mabry, Samuel J.; Cao, Xixi; McMillan, Clara; Woynaroski, Tiffany G.; Harrison, Fiona E.; Reddy, India A.; Matthies, Heinrich J. G.; Flynn, Charles R.; Wallace, Mark T.; Wu, Hui; Galli, Aurelio (Frontiers in Psychiatry, 2021)
Background Altered dopamine (DA) signaling has been associated with autism spectrum disorder (ASD), a neurodevelopmental condition estimated to impact 1 in 54 children in the United States. There is growing evidence for alterations in both gastrointestinal function and oral microbiome composition in ASD. Recent work suggests that rare variants of the SLC6A3 gene encoding the DA transporter (DAT) identified in individuals with ASD result in structural and functional changes to the DAT. One such recently identified de novo mutation is a threonine to methionine substitution at position 356 of the DAT (DAT T356M). The DAT T356M variant is associated with ASD-like phenotypes in mice homozygous for the mutation (DAT T356M+/+), including social deficits, hyperactivity, and impaired DA signaling. Here, we determine the impact of this altered DA signaling as it relates to altered oral microbiota, and metabolic and gastrointestinal dysfunction. Methods In the DAT T356M+/+ mouse, we determine the oral microbiota composition, metabolic function, and gastrointestinal (GI) function. We examined oral microbiota by 16S RNA sequencing. We measured metabolic function by examining glucose tolerance and we probed gastrointestinal parameters by measuring fecal dimensions and weight. Results In the DAT T356M+/+ mouse, we evaluate how altered DA signaling relates to metabolic dysfunction and altered oral microbiota. We demonstrate that male DAT T356M+/+ mice weigh less (Wild type (WT) = 26.48 ± 0.6405 g, DAT T356M+/+ = 24.14 ± 0.4083 g) and have decreased body fat (WT = 14.89 ± 0.6206%, DAT T356M+/+ = 12.72 ± 0.4160%). These mice display improved glucose handling (WT = 32.60 ± 0.3298 kcal/g, DAT T356M+/+ = 36.97 ± 0.4910 kcal/g), and an altered oral microbiota. We found a significant decrease in Fusobacterium abundance. Fusobacteria is an anaerobic bacterium that is implicated in multiple diseases. The abundance of Fusobacterium was associated with improved glucose handling and decreased body fat. Conclusions Our findings provide new insights into how DAT dysfunction may alter gastrointestinal function, composition of the oral microbiota, and metabolism. Our data suggest that impaired DA signaling in ASD is associated with a number of metabolic and gastrointestinal changes which are common in individuals with ASD.